First demonstration of intrafractional tumor‐tracked irradiation using 2D phantom MR images on a prototype linac‐MR. Issue 5 (30th April 2013) - Yun, Jihyun; Wachowicz, Keith; Mackenzie, Marc; Rathee, Satyapal; Robinson, Don; Fallone, B. G.
Abstract : Purpose: : To demonstrate intrafractional MR tumor tracking using a prototype linac‐MR by delivering radiation to a moving target undergoing simulated tumor motions. Methods: : A prototype linac‐MR at the Cross Cancer Institute was used for intrafractional MR imaging and simultaneous beam delivery. A Varian 52‐leaf MK‐II multileaf collimator (MLC) was used for beam collimation. The authors used an inhouse built MR compatible motion phantom to simulate tumor motions during tracking with two different motion patterns (sine and modified cosine). Gafchromic film was inserted in the phantom to measure radiation exposure, and this film measurement was converted to dose (cGy) for further analysis. The authors demonstrated intrafractional tracking in various scenarios: [Scenario 0 (S0)] no phantom motion + no beam margin, (S1) no phantom motion + maximum beam margin, (S2) phantom motion + no beam margin, (S3) S2 + MLC tracking, and (S4) S3 + motion prediction. S0 emulates a perfect tumor tracking scenario, and its result was used as a "gold‐standard" to evaluate tracking accuracy from other scenarios. The authors compared (1) time difference in phantom and MLC motion curves in S3 and S4, and (2) dose profiles (50% beam width, 80%–20% penumbra width) from scenarios S1–S4 to S0. Results: : In S4, no observable time difference exists between the phantom and MLC motion curves, indicating that MLC tracks phantom motion accurately. Comparing S4 to S0, 50% beam width reveals minimal differences of < 0.5 mm, while the increase in 80%–20% penumbra width is limited to 0.4 and 1.7 mm in the sine and modified cosine patterns, respectively. Conclusions: : The authors report the first demonstration of intrafractional tumor tracking using 2D MR images. During 2 min of tracking, the authors delivered highly conformal dose to a moving target that simulates tumor motions. Compared to static target irradiation, the 50% beam width remains essentially the same (within 0.5 mm), with an increase in 80%–20% penumbra width of less than 1.7 mm in moving target irradiation. These results illustrate potential dosimetric advantages of intrafractional MR tumor tracking in treating mobile tumors as shown for the phantom case.